Stability Chaos and Periodic Solution of Delayed Rational Recursive Sequence - Abdul Khaliq; Mubeen Alam; Sk. Sarif Hassan (Pan-American Journal of Mathematics)
In this paper, we will investigate a non-linear rational difference equation of higher order. Our concentration is on invariant intervals, periodic character, the character of semi cycles and global asymptotic stability of all positive solutions of